Foundations of addictions counseling - Capuzzi, Dave; Stauffer, Mark D. (Pearson A and B, 2008)
History and etiological models of addiction / David Capuzzi and Mark D. Stauffer -- Substance and process addictions / Laura Veach and Emeline P. Gamb -- Professional issues / Melinda Haley -- Assessment : an overview / Mark D. Stauffer, David Capuzzi, and Holly Tanigoshi -- Assessment and diagnosis of addictions / John M. Laux and Dilani M. Perera-Diltz -- Motivational interviewing / Lisa Langfuss Aasheim and Heidi Wallace -- Other psychotherapeutic approaches / Cynthia J. Osborn --